(untitled) (Journal of Educational Data Mining, 2013)
Our article introduces the Journal of Educational Data Mining’s Special Issue on Educational Data Mining on Motivation, Metacognition, and Self-Regulated Learning. We outline general research challenges for data mining researchers who conduct investigations in these areas, the potential of EDM to advance research in this area, and issues in validating findings generated by EDM.